Ultra-wide-band modulation (UWB) modulation techniques for signal extraction from biomedical implants - Khan, Sheroz (s.n, 2012)
This project presents the design, working principle, simulation results and analysis of a sub-nanosecond pulse generator. This design is a mix of devices and ideas derived from contemporary reported works with result showing up ringing both at the leading and trailing ends of the pulse